Internal factors influencing customer attitude, purchase intention and purchase behaviour with regard to green personal care products. A literature review - Szaban, Marta (Publishing House of Wroclaw University of Economics and Business, 2023)
Purpose: This paper proposes an umbrella term for personal care products with green attributes and contributes a systematised review of the existing research into the factors which influence the attitude, purchase intention and purchase behaviour with regard to this product category. Study design/methodology/approach: This research literature review uses the most popular databases that compile articles from between 2007 and 2021, published in peer-reviewed scientific journals. Findings: The findings indicate that the focus of the reviewed studies was predominantly placed on analysing factors that influence either the attitude or purchase intention, and less often on purchase behaviour. Additionally, it was determined that health consciousness and appearance awareness are factors which are in need of further investigation with respect to their direct relation to the attitude and purchase intention towards green personal care products. Originality/value: This meta-analysis of the literature is the first systematisation of research on the determinants of green consumption with a hierarchical breakdown of the effects on attitude, intention, and purchasing behaviour within a single green product category. It provides valuable insights into the discussion on the attitude-behavioural gap. Addressing this gap will allow communities to transition to sustainable consumption more effectively. Research limitations/implications: The small number of identified empirical studies within the research field resulted in identifying a promising number of research gaps to be addressed in future. Practical implications: This study will be of value to marketing practitioners in relation to shaping effective marketing strategies in the green personal care products market.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 233-262
Keywords: green personal care products; sustainable consumption; attitude; purchase